Effect of iron oxide nanoparticles on vascular function and nitric oxide production in acute stress-exposed rats - Líšková, S; Bališ, P; Mičurová, A; Kluknavský, M; Okuliarová, M; Puzserová, A; Škrátek, M; Sekaj, I; Maňka, J; Valovič, P; Bernátová, I (Physiological research, 2020)
We investigated whether polyethylene glycol-coated Fe3O4 nanoparticles (IONs), acute stress and their combination modifies vascular functions, nitric oxide synthase (NOS) activity, mean arterial pressure (MAP) as well as hepcidin and ferritin H gene expressions in Wistar-Kyoto rats. Rats were divided into control, ION-treated rats (1 mg Fe/kg i.v.), repeated acute air-jet stress-exposed rats and IONs-and-stress co-exposed rats. Maximal acetylcholine (ACh)-induced and sodium nitroprusside (SNP)-induced relaxations in the femoral arteries did not differ among the groups. IONs alone significantly elevated the N?-nitro-L-arginine methyl ester (L-NAME)-sensitive component of ACh-induced relaxation and reduced the sensitivity of vascular smooth muscle cells to SNP. IONs alone also elevated NOS activity in the brainstem and hypothalamus, reduced NOS activity in the kidneys and had no effect in the liver. Acute stress alone failed to affect vascular function and NOS activities in all the tissues investigated but it elevated ferritin H expression in the liver. In the ION-and-stress group, NOS activity was elevated in the kidneys and liver, but reduced in the brainstem and hypothalamus vs. IONs alone. IONs also accentuated air-jet stress-induced MAP responses vs. stress alone. Interestingly, stress reduced ION-originated iron content in blood and liver while it was elevated in the kidneys. In conclusion, the results showed that 1) acute administration of IONs altered vascular function, increased L-NAME-sensitive component of ACh-induced relaxation and had tissue-dependent effects on NOS activity, 2) ION effects were considerably reduced by co-exposure to repeated acute stress, likely related to decrease of ION-originated iron in blood due to elevated decomposition and/or excretion.
Keywords: Rats, Inbred WKY; Stress, Physiological; cévní endotel; Nitric Oxide Synthase; mužské pohlaví; Rats; synthasa oxidu dusnatého; Magnetic Iron Oxide Nanoparticles; zvířata; Endothelium, Vascular; oxid dusnatý; magnetické nanočástice oxidů železa; fyziologický stres; Nitric Oxide; potkani inbrední WKY; krysa rodu Rattus; Male; Animals